An unusual clue in the diagnosis of primary Sjogren’s syndrome - Elena Juganaru; Claudia Cobilinschi; Ciprian Jurcut; Andreea Birlez; Daniela Opris-Belinski; Andra Balanescu (Romanian Journal of Rheumatology, 2023)
Sjogren’s syndrome (SSj) is a chronic autoimmune disease mainly targeting the exocrine glands, but sometimes associating extra-glandular manifestations. Xerosis, purpura, Raynaud’s phenomenon, cutaneous vasculitis, annular erythema are the main forms of skin involvement. A 26-year-old female patient was admitted for diffuse erythematous rash and angioedema, xerophthalmia and symmetrical arthralgia of hand joints. Anti-nuclear antibodies, anti-SSA and anti-Ro52 antibodies were identified, Schirmer’s test was positive, thus the diagnoses of primary SSj and associated urticarial vasculitis were established. Treatment with oral methylprednisolone, azathioprine and hydroxychloroquine was initiated, with favourable response over the next week. Patients with primary SSj that develop cutaneous vasculitis, lymphadenopathies or lymphopenia may be at risk for additional extra-glandular manifestations, including non-Hodgkin lymphoma.